Dysgerminoma ovarian General Hospital in Arequipa - Lozada Stanbury, B. (2015)
The authors have studied three cases of dysgerminoma of the ovary occurred between 171 ovarian tumors at the Hospital General of Arequipa, Perú; this number means an incidence of 9.67% between the 31 malignant tumors of the ovary. All the women were between 14-20 years of age and did not present menstrual disturbance; the clinical picture was abdominal distension and pain and none of hem presented virilization; the surgical treatment, in two cases was conservative, however, the verified survival was 3 years in these two patients.